Regular Physical Activity and Exercise in Prevention and Management of Diabetes Melitus - Tunde, Gbonjubola Yusuff; Abubakar, Ibrahim Ahmad (Journal of Pharmacy Practice and Community Medicine)
Dear Editor,Diabetes Mellitus (DM) is a group of metabolic diseases characterized by chronic hyperglycemia resulting from defects in insulin secretion, insulin action, or both.[1] The national Diabetes Data Group (2000) indicated that DM consists of three different types, which include: Type 1, Type 2 and gestational diabetes.[2]